Evaluating the Impact of Organic Fertilizers on Crop Yields, Soil Health, and Environmental Sustainability in Agriculture - Gomes, Ferry Yulius; Masdi, Jonner; Harunisa, Johnston (Intitute of Computer Science (IOCS), 2024)
This research investigates the application of organic fertilizers as a sustainable alternative to chemical fertilizers in agriculture, focusing on their effectiveness in enhancing crop yields, improving soil health, and promoting environmental sustainability. Through a comprehensive analysis of various studies and empirical data, the research highlights the significant long-term benefits of organic fertilizers, including improved soil structure, enhanced nutrient retention, and increased microbial biodiversity. While initial crop yield improvements with organic fertilizers may be less pronounced compared to chemical counterparts, sustained application leads to healthier soils and greater resilience against environmental stresses. Additionally, the economic viability of organic fertilizers is evaluated, revealing their potential to reduce long-term input costs and increase profitability for farmers through access to premium markets. The environmental benefits, such as reduced nutrient runoff, lower carbon footprints, and improved water quality, further underscore the importance of organic fertilizers in promoting ecological health. Ultimately, this research advocates for the adoption of organic fertilizers as a crucial strategy for fostering sustainable agricultural practices that benefit farmers, consumers, and the environment. By highlighting the interplay between economic and environmental factors, this study contributes to the ongoing discourse on sustainable agriculture and emphasizes the need for supportive policies and educational initiatives to facilitate the transition to organic practices.